Historical outbreak of Salmonella hadar. Issue 2 (October 2015) - Deshpande, A.; Curran, E.T.; Jamdar, S.; Inkster, T.; Jones, B.L.
Summary Background This article reports a historical outbreak of Salmonella hadar in a maternity setting. The outbreak occurred following admission of an infected index case, with transmission to 11 other individuals over a three-month period in a maternity and neonatal unit. Methods Despite rigorous assessment of clinical practices, screening of patients and staff, and review of disinfection and sterilization policies, the outbreak was difficult to control. This possibly reflects the capacity of S. hadar to survive well in the environment, and cause prolonged and asymptomatic carriage with intermittent shedding. Findings It is likely that the index case was a mother who had contracted infection after eating suspect food. Additionally, infection may have been perpetuated by shared use of tubes of yellow soft paraffin for lubrication of digital rectal thermometers. Conclusion This outbreak emphasizes the difficulties in controlling outbreaks of S. hadar infection in an obstetric/neonatal setting, and also emphasizes the importance of early stool sampling in any patient with diarrhoeal symptoms.